UNSUR KRIMINALITAS DALAM NOVEL ORANG-ORANG BIASA KARYA ANDREA HIRATA - Agus Yulianto (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2019)
The objective of this study is to describe the forms of crime in the novel Orang-Orang Biasa by Andrea Hirata and the factors that drive someone does a crime. The problems of the study are how the forms and the factors behind the criminality in the novel Orang-Orang Biasa by Andrea Hirata. This study uses a descriptive qualitative method with library research technique and literary sosiologi approach. The results of the analysis show that the forms of criminality in the novel are as follows. 1) Violent crimes in the form of group attack and beatings; 2) corruption; 3) money laundering; 4) theft and robbery; 5) bribery; and 6) cyber crime. The factors behind the crimes in this novel are psychological and economic factors.